Tax Auditor Team Leader’s Quality, Time Budget Pressure, Task Complexity: How Well Tax Audit Quality in Indonesia? - Nor, Aji M. Elvin; Firmansyah, Amrie; Arham, Amardianto; Vito, Bernadi (Jurnal Akuntansi dan Bisnis, 2021)
This study's objective empirically analyzes the effect of tax auditor team leader's technical competence and experience, time budget pressure, and task complexity on tax audit quality. This study employs secondary data from Indonesia Tax Authority Office. The population in this research is the Tax Assessment issued throughout Indonesia. The sample used amounted to 4,326 observations divided into two regional categories: Java Area and non-Java Area. The data are analyzed by logistic regression. The results suggest that the tax auditor team leader's technical competence, time budget pressure, and task complexity are negatively associated with tax audit results. In contrast, the tax auditor team leader experience is positively associated with the tax audit results quality. This study shows that it is essential that the Indonesian Tax Authority rearrange the tax auditor quality criteria in its regulations.